Penerapan Kombinasi Tiga Media Filtrasi Berbasis Bahan Lokal untuk Peningkatan Kualitas Air Bersih di Desa Karangluas, Kabupaten Purworejo - Dessy Isfianadewi; Hamel Farid; Ahmad Syakuri; Ady Guswady; Yusuf Sudrajat (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Access to clean water remains a challenge for residents of Karangluas Village, Kemiri District, Purworejo Regency, Central Java, Indonesia. Water from wells and communal storage tanks still contains suspended particles and fine sediments, making it appear turbid and less suitable for household use. This community service project aimed to apply a simple water filtration system using locally available materials through a combination of zeolite, coconut coir, and aquadine media. The program was conducted from August to September 2025 and involved 25 local participants in a training and hands-on workshop held at the Karangluas Village Hall. Laboratory analysis indicated that the filtration system reduced total dissolved solids (TDS) by 16.7%, iron (Fe) by more than 50%, and Escherichia coli bacteria by 35.3%. Although turbidity and manganese (Mn) levels were below the instrument’s quantification limit (<2.86 NTU), the filtered water met most parameters of the national clean water quality standards (Minister of Health Regulation No. 2 of 2023). Socially, the program increased public awareness of household water treatment and encouraged community members to replicate and maintain the filtration units independently. These results highlight the potential of locally based filtration technology to improve water quality, public health, and the sustainability of community-level water management.